The Social Movement of the Wayang Sampah Association in Raising Community Environmental Awareness - Luthfiyah Jasmine; Yosafat Hermawan Trinugraha (Equilibrium: Jurnal Pendidikan, 2024)
This research explores the role of the Wayang Sampah Association in raising environmental awareness and influencing public behavior through traditional Javanese puppetry and gamelan performances. Using a qualitative descriptive method, the study delves into how cultural education drives environmental stewardship. Data was collected from June to August 2024 through direct observation, interviews, and photo documentation, focusing on participants in the association's workshops and performances. The inductive analysis revealed that the Wayang Sampah Association effectively integrates cultural traditions with environmental advocacy, resulting in heightened public awareness and more sustainable waste management practices within the community. The study underscores the significance of culturally resonant approaches in promoting long-term environmental change, illustrating how traditional arts can foster a deeper understanding of environmental issues and inspire actionable change. These findings contribute to the broader discourse on the effectiveness of New Social Movements in tackling contemporary environmental challenges, emphasizing the potential of cultural integration in achieving sustainable outcomes.